STUDY KOMPARASI KINERJA GURU SEBELUM DENGAN SESUDAH SERTIFIKASI DI SMPN 1 KECAMATAN UTAN - Abdul Rahim; Yayat Fitriani; Siti Aisyah; K Kamaruddin (Fakultas Ekonomi dan Manajemen, 2021)
The purpose of this study was to know the comparison of teacher performance before and after certification at SMPN 1, Utan Sub-District. Type of this study was comparative study. The type of data used in this study was quantitative data in the form of data on the number of teacher performance scores before and after certification at SMP Negeri 1, Utan Sub-District. The source of the data used was secondary data obtained through the collection of administrative of work implementation appraisal document (DP3) at SMP Negeri 1 Utan Sub-District. Data analysis method using two difference test analysis means (paired sample test). Based on the results of data analysis, showed that there was a difference between the performance of teachers at SMPN 1 in Utan District before and after certification. Teacher performance at SMPN 1 in Utan Sub-District increased after certification. This was indicated by the value work implementation appraisal document (DP3) of teachers at SMPN 1 in Utan District after certification was higher than before certification.